1994
DOI: 10.1016/0304-3959(94)90221-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain after soft-tissue injury of the cervical spine: trapezius muscle blood flow and electromyography at static loads and fatigue

Abstract: Microcirculation in the upper portion of the right and left trapezius muscles was measured percutaneously by laser-doppler flowmetry (LDF) during two 10-min-long series of alternating 1-min periods of static contraction and rest determined electromyographically (EMG). Twenty-five patients with pain persisting after a soft-tissue injury of the neck were studied. Pain assessments by using visual analogue scales and drawings showed 13 patients with predominantly unilateral and 12 with bilateral neck-shoulder pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 11 publications
3
23
1
Order By: Relevance
“…Comparable results were also reported by Westgaard et al (2001) who did not Wnd signiWcantly increased EMG activity of the trapezius muscles in subjects with neck-shoulder pain, and Larsson et al (1994) only found a tendency towards an increase in RMS values in chronic WAD patients. In addition Holte and Westgaard (2002) found that WMSD patients were not necessarily characterised by increased muscle activity levels.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Comparable results were also reported by Westgaard et al (2001) who did not Wnd signiWcantly increased EMG activity of the trapezius muscles in subjects with neck-shoulder pain, and Larsson et al (1994) only found a tendency towards an increase in RMS values in chronic WAD patients. In addition Holte and Westgaard (2002) found that WMSD patients were not necessarily characterised by increased muscle activity levels.…”
Section: Discussionsupporting
confidence: 87%
“…However not all studies report such clear diVerences between activity levels in pain patients and healthy controls (e.g. Larsson et al 1994).…”
Section: Introductionmentioning
confidence: 94%
“…Larsson and coworkers (Larsson et al 1999(Larsson et al , 1994 have reported lower blood fluxes in the painful muscles. It is worth noting that they applied absolute flux units in their analysis, and only normalized across experimental conditions within each individual (Larsson et al 1999(Larsson et al , 1993b.…”
Section: Discussionmentioning
confidence: 97%
“…This method has proven valid in animal studies (Stern 1975), and has been applied in humans. Larsson and coworkers have reported laser-Doppler measures of blood flux in both healthy subjects and subjects with various pain conditions (Larsson et al 1993a(Larsson et al , 1994. Their results suggested that blood flux might be inadequate relative to metabolic demands during higher-level static contractions.…”
Section: Introductionmentioning
confidence: 96%
“…In a series of studies, Larsson and colleagues investigated local microcirculation using laser Doppler flowmetry in patients with chronic neck pain. During static contractions, reduced microcirculation was observed in painful muscles among patients (Larsson et al 1994). In addition, a greater reduction in blood flow was associated with a higher pain intensity and mitochondrial changes in patients (Larsson et al 1990).…”
Section: Autonomic Aberrations In Chronic Neck-shoulder Pain: Recent mentioning
confidence: 96%